Improving Disaster Resilience in Small Islands: Sustainable Strategies for Adaptation and Mitigation - Nashihah, Durratun; Hanafi, Imam; Dhulhijjayani, Firdausi (Journal of Transformative Governance and Social Justice, 2023)
Bawean is a small island where it is the pulse point of the Indonesian Archipelago which is located in the middle of the archipelago and right on the equator. The objectives of this study are Analyzing socio-ecological systems, resilience as a concept is crucial, especially in the context of robustness, vulnerability, and sustainability. This research method includes: (1) Research Question is a stage where the author explains the core problems that will be studied in this paper; (2) Quality Assessment, is a stage carried out by researchers to identify potential literature related to the title presented; (3) Data Extraction, is a stage carried out to select the literature used and examine more deeply related to the observed object; (4) Data Synthesis and Analysis, knowing interpretations related to A Socio-Ecological Systems Approach Disaster Resilience for Small Islands and to detect follow-up to performance findings. The conclusion in this discussion refers to three topics related to social resilience, namely related processes that pay particular attention to human resilience in order to improve human capacity to recover from disasters in the shortest amount of time, related to ecological resilience, where ecological resilience is the maximum amount of energy or disturbance that a system can tolerate before experiencing a shift in its stability domain, and related to economic resilience, where it relates International organizations, academics, and policymakers are starting to appreciate the importance of community resilience